A prospective study of hypothyroidism during pregnant attending tertiary care hospital in south India - Sravani, G.; Smitha, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Disorder of thyroid function is common during pregnancy and hypothyroidism is more common then hyperthyroidism affecting 3–5% of all pregnant women. Maternal hypothyroidism is associated with both maternal adverse effects like preeclampsia, ecclampsia, pregnancy induced hypertension and gestational diabetes mellitus and foetus complication like low birth weight, pre term birth, neurological deformities and abnormal presentation. Methods: In present study 120 patients with overt and subclinical hypothyroidism were included in this study. Detailed histories of patients were taken and clinical examination was done and data was collected in a predesigned Performa. We used standard diagnostic criteria for diagnosis of overt and subclinical hypothyroidism. Results: Pregnancy induced hypertension was found in 10% patient, Chronic hypertension was present in 1.6% patients, abortion in second trimester 1.6% patients, incomplete abortion in 4.18% patients. Missed abortion was present in 2.5% patients. Conclusions: Hypothyroidism during pregnancy is more common in primi. Most common age group was third decade and was commonly detected before 10 weeks of gestation. Pregnancy induced hypertension, oligohydramnios and preterm delivery was more common than abortion in second trimester and missed abortion.